White carbon black dispersibility identification method and system based on dynamic light scattering and small-angle X-ray scattering combined analysis
Through the combined analysis of dynamic light scattering and small-angle X-ray scattering, the dispersion of white carbon black in rubber is evaluated, which solves the complex and high-cost problems of traditional methods, and achieves rapid and accurate dispersion evaluation, which is suitable for industrial production.
Patent Information
- Application Number
- CN202510231952.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-06-03
AI Technical Summary
The prior art is difficult to effectively evaluate the dispersion of white carbon black in rubber, and the traditional methods are complex, costly and difficult to widely use in industrial production.
A dispersion scoring system was formulated by a combined analysis method of dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) by comprehensively evaluating the particle size, particle size distribution width, aggregation degree and diffraction characteristics of the aggregated particles.
It realizes scientific, rapid and accurate evaluation of the dispersion of white carbon black, provides quantitative dispersion evaluation data, is suitable for quality control in industrial production, and improves the performance of rubber products.
Smart Images

Figure CN120084831A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tire detection, and in particular, to a method and system for identifying the dispersion of silica based on the combined analysis of dynamic light scattering and small-angle X-ray scattering. Background Art
[0002] In the rubber tire industry, the mainstream reinforcing materials of rubber are divided into two categories: carbon black and silica. Compared with traditional carbon black, silica is widely used in the tire field due to its unique low rolling resistance and high wet grip. However, due to the large number of hydroxyl groups on the surface of silica, which have strong polarity, these hydroxyl groups attract each other, easily causing flocculation between silica particles. The agglomerated silica after flocculation requires a very strong shear force to be broken open. At the same time, since the medium in which silica is dispersed is non-polar rubber, the polar silica and non-polar rubber repel each other, further increasing the difficulty of opening the agglomerated silica. Since it is very difficult to break open the agglomerated silica, in the tire and product industries, the dispersion of silica in rubber is very difficult.
[0003] Two key indicators affecting the performance of silica are the specific surface area and particle size of silica. The specific surface area of silica determines the reinforcing performance of silica. The higher the specific surface area, the better the reinforcing performance. The particle size of silica determines the dispersion performance of silica. The larger the particle size, the stronger the dispersion ability.
[0004] The dispersion degree of silica in rubber largely determines the performance of the rubber compound. Generally speaking, in the silica system formulation, the better the dispersion of silica, the more excellent the physical and dynamic properties of the rubber compound. In order to improve the dispersion ability of silica, various silica manufacturers have successively launched so-called highly dispersed silica, and its mechanism is to adjust the aggregate structure of silica and increase the particle size of silica on the premise of ensuring the specific surface area of silica, thereby improving the dispersion of silica.
[0005] There has never been a clear definition on how to distinguish ordinary silica from highly dispersed silica. In the rubber industry, the Payne effect is generally used to characterize the dispersion ability of silica. The Payne effect refers to a phenomenon in which the dynamic modulus of filled rubber decreases sharply with the increase of strain. The higher the value of the Payne effect, the worse the dispersion ability of silica.
[0006] Traditionally, the detection of the dispersion of silica mainly relies on surface analysis techniques such as scanning electron microscopy (SEM) and transmission electron microscopy (TEM). These methods can indirectly evaluate the dispersion through morphology observation. However, these techniques not only require complex sample preparation, but also often difficult to provide quantitative dispersion data, and the testing time is long and the cost is high, making it difficult to be widely used in industrial production.
[0007] To test the Payne effect of silica, it is necessary to mix silica with rubber, processing aids, etc. to form a mixed rubber for testing. A large number of equipment and raw materials are required (mixing equipment: internal mixer, open mill, etc.; testing equipment: RPA2000, etc.; raw materials: various rubbers, processing aids, etc.). Moreover, since raw materials other than silica are needed in the test, the mixing process also has a great impact on the dispersion degree of silica. Therefore, the data reproducibility of the Payne effect test is not high.
[0008] For example, in a method for evaluating the dispersion degree of silica in a rubber compound in a Chinese invention patent application (publication number: CN113884664A, publication date: January 4, 2022) applied by the applicant, the method includes the following steps: 1) Obtain the flow value F, the standard flow value F standard, and the flow value Fnosilane; 2) Based on the dispersion degree of silica based on the flow value, calculate the dispersion degree D according to the formula; the smaller the dispersion degree D, the better the dispersion of the surface silica. This patent uses a rubber compound flow analyzer to test the flow value of the rubber compound to evaluate the agglomeration degree of the filler network in the silica formula, and then evaluate the dispersion degree of silica. In a Chinese invention patent application (publication number: CN116577247A, publication date: August 11, 2023) applied by the applicant, a detection method for detecting the dispersion performance of silica, this method destroys the aggregates of silica by ultrasonic oscillation in an aqueous medium, uses a laser particle size distribution analyzer to record the volume average particle size of silica under different ultrasonic oscillation times, and fits a y = kx + b curve with time as the abscissa and volume average particle size as the ordinate. The greater the absolute value of the slope k, the stronger the dispersion ability of silica.
[0009] Dynamic light scattering (DLS) technology can measure the particle size distribution in the liquid phase in real time and can quantify the dispersion state of particles; while small-angle X-ray scattering (SAXS) technology can effectively reflect the aggregation degree of particles and provide intuitive information about particle aggregation phenomena through the analysis of the intensity and width of diffraction peaks. However, at present, the research on the combined application of these two technologies in the evaluation of silica dispersion is still in its infancy, lacking a systematic and standardized method that can take into account both the particle size distribution and the aggregation degree of particles to provide accurate and operable dispersion evaluation data. Summary of the Invention
[0010] In order to solve the above technical problems, the purpose of the present invention is to provide a method for identifying the dispersion of silica based on the combined analysis of dynamic light scattering and small-angle X-ray scattering. By comprehensively evaluating the particle size, particle size distribution width, aggregation degree, and diffraction characteristics of aggregated particles of silica, a quantitative dispersion scoring system is proposed, aiming to provide a scientific, fast, and accurate dispersion evaluation tool for the rubber industry, especially with broad application prospects in high-demand industrial production processes such as tire manufacturing.
[0011] To achieve the above object, the present invention adopts the following technical solutions: A method for identifying the dispersibility of silica based on the combined analysis of dynamic light scattering and small angle X-ray scattering, comprising the following steps: 1) Prepare a silica sample to be tested, and uniformly mix it with a rubber matrix to form a composite material. After mixing, perform pretreatment with a solvent to ensure the uniformity of the sample; 2) Use dynamic light scattering (DLS) to measure the particle size distribution of silica particles in the composite material, and record the DLS average particle size and the (SAXS) particle size distribution width; 3) Use small angle X-ray scattering (SAXS) to measure the aggregation degree of silica particles in the composite material, and record the intensity and width of the SAXS diffraction peak; 4) Evaluate the dispersibility of silica according to the DLS and SAXS test results, and formulate a dispersibility determination standard; Dispersibility score = (DLS average particle size × 0.4) + (DLS particle size distribution width × 0.3) + (SAXS diffraction peak intensity × 0.2) + (SAXS diffraction peak width × 0.1); Good dispersibility: The dispersibility score is between 0 and 10; Average dispersibility: The dispersibility score is between 10 and 20; Poor dispersibility: The dispersibility score is greater than 20.
[0012] Preferably, the silica sample is highly dispersed silica or surface-treated silica.
[0013] Preferably, the rubber matrix is natural rubber, synthetic rubber or a mixture thereof.
[0014] Preferably, the addition amount of silica is 50 - 80 parts per 100 parts by weight of rubber.
[0015] Preferably, the solvent is selected from one or more of ethanol, isopropanol, n-butanol, acetone, toluene, dichloromethane and cyclohexane.
[0016] Furthermore, the present invention also provides a system for identifying the dispersibility of silica, which implements the above method, comprising: 1) A dynamic light scattering instrument for measuring the particle size distribution of silica particles in the composite material and recording the average particle size and the particle size distribution width; 2) A small angle X-ray scattering instrument for measuring the aggregation degree of silica particles in the composite material and recording the intensity and width of the diffraction peak; 3) A control unit for calculating the dispersibility score according to the DLS and SAXS test results and outputting a dispersibility evaluation result according to a predetermined standard.
[0017] Furthermore, the present invention also provides the use of the described identification method for detecting the dispersibility of silica during the tire production process.
[0018] The method for identifying the dispersibility of silica based on the combined analysis of dynamic light scattering (DLS) and small-angle X-ray scattering (SAXS) provided by the present invention has the following remarkable technical effects: 1. Efficient and accurate dispersibility evaluation: By combining the DLS and SAXS techniques, the present invention can comprehensively and quantitatively evaluate the dispersibility of silica in the rubber matrix. The DLS technique can accurately measure the particle size and particle size distribution of silica particles, while the SAXS technique can evaluate the degree of particle aggregation. The two complement each other, providing comprehensive quantitative data for dispersibility and avoiding the limitations of relying on visual judgment and qualitative analysis in traditional methods.
[0019] 2. Scientific basis for optimizing rubber formulations: The present invention provides a clear dispersibility scoring system. By combining DLS and SAXS data, it can effectively provide a scientific basis for optimizing rubber formulations. By accurately evaluating the dispersibility of silica, it can help rubber manufacturers adjust the formulation and improve the performance of rubber products. Especially in the manufacture of high-demand rubber products such as tires and hoses, it can enhance wear resistance, grip, and service life.
[0020] 3. Rapid detection method suitable for industrial production: Compared with traditional microscopy observation methods, the method of the present invention has higher working efficiency and lower cost. The DLS and SAXS techniques can achieve rapid and automated detection, enabling real-time and routine dispersibility detection during industrial production processes to meet the quality control requirements in large-scale production.
[0021] 4. Quantitative dispersibility scoring: By comprehensively considering the particle size, particle size distribution, and degree of aggregation of particles, the dispersibility scoring system proposed by the present invention (dispersibility score = DLS average particle size × 0.4 + DLS particle size distribution width × 0.3 + SAXS diffraction peak intensity × 0.2 + SAXS diffraction peak width × 0.1) can standardize and quantify the dispersibility evaluation, avoiding subjective errors in traditional methods and providing an accurate quantitative standard for dispersibility detection during the production process.
[0022] Through the accurate evaluation of the dispersibility of silica, the present invention can effectively reduce the agglomeration phenomenon of silica particles, ensure their uniform distribution in the rubber matrix, thereby enhancing the mechanical properties, durability, and thermal stability of rubber products. Especially in the tire industry, it helps to improve the performance and service life of tires. Brief Description of the Drawings
[0023] Figure 1 The DLS graph obtained for Example 1.
[0024] Figure 2 SAXS pattern obtained for Example 1. Detailed implementation manners
[0025] Combined with the embodiments of the present invention below, the technical solutions in the embodiments will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0026] This experiment aims to verify the accuracy and practicability of the evaluation method for the dispersibility of silica based on the combined analysis of DLS and SAXS, and evaluate its application effect in rubber formulations by comparing with traditional dispersibility evaluation methods.
[0027] 1. Sample preparation Sample selection: Product A: Highly dispersed silica (for Example 1) Product B: Untreated silica (Comparison 1) Product C: Surface-treated silica (for Example 2) Product D: Ordinary silica (Comparison 2) Product E: Ordinary silica (for Example 3) Product F: Ordinary silica (Comparison 3) Rubber matrix: Natural rubber (NR) and synthetic rubber (SBR) Mixing ratio: The weight ratio of each silica to the rubber matrix is 60:100 (silica:rubber matrix) Pretreatment: The mixed samples are treated with cyclohexane as a solvent to ensure the uniform dispersion of silica particles in the rubber matrix.
[0028] 2. Test steps DLS test: Use a dynamic light scattering instrument (Malvern Zetasizer Nano) to measure the particle size distribution of each sample, and record the DLS average particle size and the particle size distribution width.
[0029] SAXS test: Use a small angle X-ray scattering instrument (X'Pert PRO) to test the diffraction peak intensity and width of each sample, and evaluate the degree of particle aggregation.
[0030] Dispersibility score: Calculate the dispersibility score of each sample based on the following formula: Dispersibility score = (DLS average particle size × 0.4) + (DLS particle size distribution width × 0.3) + (SAXS diffraction peak intensity × 0.2) + (SAXS diffraction peak width × 0.1).
[0031] Data analysis: Analyze the dispersibility scores of each sample, and determine the dispersibility level according to the score: Good dispersibility: The dispersibility score is between 0 and 10; Average dispersibility: The dispersibility score is between 10 and 20; Poor dispersibility: The dispersibility score is greater than 20.
[0032] 3. Comparative experiment Traditional dispersibility test: Use a scanning electron microscope (SEM) and a transmission electron microscope (TEM) to observe the morphology of the silica particles in each sample, and evaluate the dispersion of the particles.
[0033] Comparison result: Compare the combined analysis result of DLS and SAXS with the observation result of the traditional dispersibility test to verify the accuracy of the method of the present invention.
[0034] Example 1: Evaluation of the dispersibility of a highly dispersed silica-rubber composite (Product A) Sample preparation: Select highly dispersed silica (Product A), and uniformly mix it with natural rubber (NR) at a weight ratio of 50 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment to ensure the uniform dispersion of the silica particles in the rubber matrix.
[0035] DLS test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of the silica particles in the composite material. The test results show that the average particle size of the silica particles is 20 nm, and the particle size distribution width is 5 nm.
[0036] SAXS test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of the silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.15 a.u., and the diffraction peak width is 0.05°.
[0037] Dispersibility score: Calculate the dispersibility score according to the DLS and SAXS test results: Dispersibility score = (20×0.4) + (5×0.3) + (0.15×0.2) + (0.05×0.1) = 9.535; Since the dispersibility score is between 0 and 10, it indicates that the composite material has good silica dispersibility.
[0038] Example 2: Evaluation of the dispersibility of a surface-treated silica-synthetic rubber composite (Product C) Sample Preparation: Select surface-treated silica (Product C) and uniformly mix it with synthetic rubber (SBR) at a weight ratio of 60 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment to ensure the uniform dispersion of silica particles in the rubber matrix.
[0039] DLS Test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of silica particles in the composite material. The test results show that the average particle size of silica particles is 15 nm, and the particle size distribution width is 4 nm.
[0040] SAXS Test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.10 a.u., and the diffraction peak width is 0.03°.
[0041] Dispersion Score: Calculate the dispersion score based on the DLS and SAXS test results: Dispersion Score = (15 × 0.4) + (4 × 0.3) + (0.10 × 0.2) + (0.03 × 0.1) = 7.223; Since the dispersion score is between 0 and 10, it indicates that the composite material has good silica dispersion.
[0042] Example 3: Evaluation of the Dispersion of a Composite Material of Ordinary Silica and Synthetic Rubber (Product E) Sample Preparation: Select ordinary silica (Product E) and uniformly mix it with synthetic rubber (SBR) at a weight ratio of 70 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment to ensure the uniform dispersion of silica particles in the rubber matrix.
[0043] DLS Test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of silica particles in the composite material. The test results show that the average particle size of silica particles is 30 nm, and the particle size distribution width is 7 nm.
[0044] SAXS Test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.20 a.u., and the diffraction peak width is 0.08°.
[0045] Dispersion Score: Calculate the dispersion score based on the DLS and SAXS test results: Dispersion Score = (30 × 0.4) + (7 × 0.3) + (0.20 × 0.2) + (0.08 × 0.1) = 14.148; Since the dispersion score is between 10 and 20, it indicates that the silica dispersion in the composite material is average.
[0046] Comparative Example 1: Evaluation of the dispersibility of untreated silica and natural rubber composite materials (Product B) Sample preparation: Select untreated silica (Product B) and uniformly mix it with natural rubber (NR) at a weight ratio of 80 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment.
[0047] DLS test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of silica particles in the composite material. The test results show that the average particle size of silica particles is 100 nm and the particle size distribution width is 25 nm.
[0048] SAXS test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.35 a.u. and the diffraction peak width is 0.20°.
[0049] Dispersibility score: Calculate the dispersibility score based on the DLS and SAXS test results: Dispersibility score = (100×0.4) + (25×0.3) + (0.35×0.2) + (0.20×0.1) = 47.590; Since the dispersibility score is greater than 20, it indicates that the dispersibility of silica in this composite material is poor.
[0050] Comparative Example 2: Evaluation of the dispersibility of ordinary silica and synthetic rubber composite materials (Product D) Sample preparation: Select ordinary silica (Product D) and uniformly mix it with synthetic rubber (SBR) at a weight ratio of 60 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment.
[0051] DLS test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of silica particles in the composite material. The test results show that the average particle size of silica particles is 80 nm and the particle size distribution width is 20 nm.
[0052] SAXS test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.30 a.u. and the diffraction peak width is 0.15°.
[0053] Dispersibility score: Calculate the dispersibility score based on the DLS and SAXS test results: Dispersibility score = (80×0.4) + (20×0.3) + (0.30×0.2) + (0.15×0.1) = 38.075; Since the dispersion score is greater than 20, it indicates that the dispersion of silica in this composite material is poor.
[0054] Comparative Example 3: Evaluation of the dispersion of a composite material of common silica and synthetic rubber (Product F) Sample preparation: Select common silica (Product F) and uniformly mix it with synthetic rubber (SBR) at a weight ratio of 70 parts / 100 parts to form a composite material. After mixing, use cyclohexane as a solvent for pretreatment.
[0055] DLS test: Use a dynamic light scattering (DLS) instrument to test the particle size distribution of silica particles in the composite material. The test results show that the average particle size of silica particles is 60 nm and the particle size distribution width is 18 nm.
[0056] SAXS test: Use a small-angle X-ray scattering (SAXS) instrument to test the aggregation degree of silica particles in the composite material. The test results show that the intensity of the diffraction peak is 0.40 a.u. and the diffraction peak width is 0.18°.
[0057] Dispersion score: According to the DLS and SAXS test results, calculate the dispersion score: Dispersion score = (60×0.4) + (18×0.3) + (0.40×0.2) + (0.18×0.1) = 29.498; Since the dispersion score is greater than 20, it indicates that the dispersion of silica in this composite material is poor.
[0058] The above test results are statistically summarized as follows: Sample Name DLS Average Particle Size (nm) DLS Particle Size Distribution Width (nm) SAXS Diffraction Peak Intensity (a.u.) SAXS Diffraction Peak Width (°) Dispersion Score SEM / TEM Observation Results Product A (Example 1) 20 5 0.15 0.05 9.535 Uniform dispersion, smaller particles Product C (Example 2) 15 4 0.10 0.03 7.223 Uniform dispersion, even smaller particles Product E (Example 3) 30 7 0.20 0.08 14.148 Relatively uniform, larger particles Product B (Comparison 1) 100 25 0.35 0.20 47.590 Particle agglomeration, poor dispersion Product D (Comparison 2) 80 20 0.30 0.15 38.075 Non-uniform particles, relatively poor dispersion Product F (Comparison 3) 60 18 0.40 0.18 29.498 Larger particles, relatively poor dispersion The results of Example 1 and Example 2 show that the silica particles have a smaller particle size and a narrower particle size distribution width, the diffraction peak intensity is lower and the width is smaller, indicating that these two samples have good dispersion, the dispersion score is between 0 and 10, meeting the standard of good dispersion, and the SEM / TEM observation results also show that the particles are uniformly dispersed.
[0059] The results of Example 3 show that although the particle size of silica is relatively large, the particle size distribution is relatively narrow and the intensity and width of the diffraction peak are lower, and the dispersion score is between 10 and 20, indicating that its dispersion is general. The SEM / TEM results show that the particles are larger, but there is still a certain degree of uniform dispersion.
[0060] The results of Comparative Experiments 1, 2, and 3 show that all the comparative samples (B, D, F) have a larger particle size, a wider particle size distribution, a higher diffraction peak intensity, a smaller width, and a dispersion score greater than 20, indicating that these samples have poor dispersion. The SEM / TEM observation results further confirm the agglomeration of silica particles in these samples and poor dispersion.
[0061] The foregoing is a description of embodiments of the present invention. Through the above description of the disclosed embodiments, those skilled in the art can implement or use the present invention. Various modifications to these embodiments will be obvious to those skilled in the art. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather will be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for identifying the dispersibility of white carbon black based on the combined analysis of dynamic light scattering and small angle X-ray scattering, characterized in that: The following steps are involved: 1) Prepare the silica sample to be tested and mix it evenly with the rubber matrix to form a composite material. After mixing, pre-treat the sample with a solvent to ensure the uniformity of the sample; 2) Use dynamic light scattering (DLS) to test the particle size distribution of silica particles in the composite material, and record the DLS average particle size and (SAXS) particle size distribution width; 3) Use small angle X-ray scattering (SAXS) to test the aggregation degree of silica particles in the composite material, and record the intensity and width of the SAXS diffraction peak; 4) Evaluate the dispersibility of silica based on the DLS and SAXS test results, and formulate a dispersibility judgment standard; Dispersibility score = (DLS average particle size × 0.4) + (DLS particle size distribution width × 0.3) + (SAXS diffraction peak intensity × 0.2) + (SAXS diffraction peak width × 0.1); Good dispersion: the dispersion score is between 0 and 10; Average dispersion: dispersion score is between 10 and 20; Poor dispersibility: Dispersibility score is greater than 20.
2. The identification method according to claim 1, characterized in that: The silica sample is highly dispersed silica or surface treated silica.
3. The identification method according to claim 1, characterized in that: The rubber matrix is natural rubber, synthetic rubber or a mixture thereof.
4. The identification method according to claim 1, characterized in that: The amount of white carbon black added is 50-80 parts per 100 parts by weight of rubber.
5. The identification method according to claim 1, characterized in that: The solvent is selected from one or more of acetone, toluene, dichloromethane and cyclohexane.
6. A system for identifying the dispersibility of white carbon black, characterized in that: The system implements the method described in any one of claims 1 to 5, comprising: 1) a dynamic light scattering instrument for measuring the particle size distribution of silica particles in a composite material, and recording the average particle size and the width of the particle size distribution; 2) a small-angle X-ray scattering instrument for measuring the degree of aggregation of silica particles in the composite material, and recording the intensity and width of the diffraction peak; 3) a control unit for calculating the dispersion score based on the DLS and SAXS test results and outputting the dispersion evaluation result according to a predetermined standard.
7. The identification method according to any one of claims 1 to 5 is used to detect the dispersibility of white carbon black in the tire production process.
Citation Information
Patent Citations
Method and equipment for evaluating dispersion degree of white carbon black in rubber material and computer readable carrier medium
CN113884664A
Detection method for detecting dispersing performance of white carbon black and application thereof
CN116577247A